Evaluasi Kinerja Seismik Struktur Atas Gedung Suzuya Pematangsiantar Menggunakan Metode Phusover - Sionmora Ritonga; Irwan Irwan (Prosiding Seminar Nasional Ilmu Teknik, 2024)
Pushover analysis is a procedure to determine the collapse behavior of a building in an earthquake. The pushover analysis method is widely used by high-level building planners who rely on performance-based planning. The aim of this research is to become a reference in evaluating the collapse performance and behavior of buildings. This research was carried out using SAP2000 software where the structure was modeled in three dimensions. After carrying out the initial load analysis and stress examination, the analysis results showed that the behavior of the building structure was non-linear. This occurs under conditions of higher loads or significant deformation. So the results obtained in the X direction, the maximum displacement value obtained is 0,014410 m achieved with a base shear of 64.746,662 kN. In step 7, collapse (C) occurs in one of the structures marked with a yellow dot. Meanwhile in the Y direction, the displacement obtained is 0,15 m with a base shear of 58.897,495 kN. Based on the structural performance classification according to ATC-40, both in the X direction and Y direction, the building structure is included in the "Immediate Occupancy" category. This means that the structure is able to maintain its function without experiencing significant damage at the given load level. This level of performance is still well below the “Collapse Prevention (CP) limit, meaning that the structure is considered safe under these conditions.